DEVELOPING INDONESIAN MSMEs EXPORT READINESS IN THE DIGITAL ERA - Nurwidyatmoko, Nurwidyatmoko; Hakimul Ikhwan; Evita Hanie Pangaribowo (International Journal of Social Science, 2026)
Indonesian MSMEs play a significant role in the economy, but the contribution of MSMEs to national non-oil and gas exports is still very low. Currently, the opportunity for MSMEs to connect to global markets is increasingly open along with the increasingly massive use of digital technology and the increasing number of free trade agreements. On the other hand, this opportunity leaves homework for each stakeholder in preparing the right strategy for developing MSME competitiveness. This research aims to explore the MSME export readiness framework that is relevant in the digital era. This study uses a qualitative method. Primary data collection was carried out through interviews with several export mentors and export practitioners and observation on export training program. Secondary data was obtained from recorded webinars related to exports and related literature. The results of this study enrich the concept of export readiness proposed by Tan et al. (2007). The development of MSME export readiness in Indonesia can begin with a presentation on stimulation that influences the internal and external readiness of MSMEs which includes awareness of export potential, being able to prepare appropriate products, understanding export fundamentals, understanding the suitable foreign markets, understanding competition, understanding export risks, and able to take advantage of government support. Exposure to this stimulation is expected to be able to form attitude commitment and encourage the readiness of MSME resources. Currently, optimizing the digitization of MSMEs plays an important role in assisting a more efficient allocation of resources in the pre-internationalization stage